Physician attire: physicians perspectives on attire in a community hospital setting among non-surgical specialties - Basil George Verghese; Sanjana Kalvehalli Kashinath; Nagesh Jadhav; Sohni Reddy; Konara Sachith Bandara; Tara Chen; Carl H. Reynolds (Greater Baltimore Medical Center, 2020)
Background Several studies have demonstrated a patient preference for physicians wearing a white coat associated with improved patient satisfaction. There are few studies on physicians' perceptions of attire mainly done in the outpatient and surgical specialties. Objective Assess non-surgical physicians' perception of attire in the hospital and to identify if any difference in the choice of attire amongst generation X and millennial physicians. Methods We surveyed 86 physicians in the hospital with six sets of pictures of commonly worn physician attires in the hospital setting with a two-part questionnaire. Key Results Formal attire with a white coat was found to be most favored, followed by formal without a white coat. Casual attire without a white coat was the least preferred across the surveyed attributes. The results were similar in generation X and millennial physicians. Only 49% concordance was observed with what physicians preferred and what they wore. Conclusion Our study showed that physicians felt wearing a white coat was the best to convey specific attributes like honesty, confidence, professionalism, among others, similar to prior studies done in patients. However, less than half of the physicians surveyed themselves followed the preferred attire.